Finding Harmony between Science and Art in Pediatric Cardiology: Acknowledging When Being "Objective" May Not Truly Be Objective - Rohit S. Loomba (MDPI AG, 2016)
As pediatric cardiologists, we greatly value objective decision-making and logic. [...]